THE EFFECTIVENESS OF USING ARTIFICIAL INTELLIGENCE ON STUDENTS' LEARNING INTEREST, CRITICAL THINKING, AND CREATIVITY IN NURSING EDUCATION - Syafriati, Ani (Rifapublisher.id, 2024)
Background: AI has been initiated in clinical practice and nursing education. The integration of artificial intelligence (AI) in nursing education will benefit practice by potentially preparing nursing students for repetitive, safe, and efficient practice. Objective: To determine the effectiveness of using artificial intelligence (AI) on students' learning interest, critical thinking, and creativity in learning in nursing education. Method: This study used a quantitative method, a post-test with randomized experimental and control groups. The sample consisted of nursing students from the Mitra Adiguna Health Science Institute in Palembang. The experimental group of 89 students received an explanation of the use of Chatbot or ChatGPT, an explanation of nursing lecture material, and completed a nursing care case study using Chatbot or ChatGPT. Meanwhile, the control group of 89 students did not use Chatbot or ChatGPT. Results: The Mann-Whitney test results in this study showed an Asymp. Sig. (2-tailed) P-value of 0.000 < 0.05, meaning that the use of artificial intelligence (AI) has proven effective in increasing students' learning interest, critical thinking, and creativity in nursing education. Conclusions: The use of artificial intelligence can be one of the methods in nursing education to increase learning interest, stimulate critical thinking, and enhance student creativity.